Pengaruh Asisten Virtual Berbasis Artificial Intelligence Terhadap Integritas Sertifikasi Kompetensi Pemrograman secara Online - Pujiono, Imam Prayogo; Rachmawanto, Eko Hari; Hana, Fida Maisa (Jurnal Kridatama Sains dan Teknologi, 2024)
The use of virtual assistants based on Artificial Intelligence (AI) has shown a significant impact in various sectors, especially education. The presence of AI-based virtual assistants capable of answering questions from various topics creates new opportunities and challenges, especially regarding exams and assessments. This research examines the impact of using AI-based virtual assistants, specifically ChatGPT (GPT-4), on the integrity of programming competency certification carried out online. Through field experiments, the author took three online programming competency certifications related to "Python Fundamentals for Beginners", "Java Programming", and "Android Application Development" and used ChatGPT (GPT-4) to answer all exam questions. The test results show that GPT-4 successfully answered 9 out of 10 questions given in the three programming competency certifications that were taken and declared to have passed the exam. This raises serious questions about the validity of certificates obtained through competency certification which is carried out online. This research reveals that there is a need for more effective examination methods in assessing the true abilities of certification participants, such as project-based examinations, examinations using questions in video form, and interview-based examinations. This examination method will not only increase the credibility of online programming competency certification but also ensure that participants who pass the certification have expertise related to the field being tested. Further research is needed to explore the impact of AI-based virtual assistants in various educational contexts, especially on online competency certification.